2005
DOI: 10.1177/1077546305056460
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Finite Element Simulations of Ground Vibration Generated by High-Speed Trains and Engineering Countermeasures

Abstract: In this paper we discuss the benefits of using rubber-modified asphalt concrete in high-speed railway foundations. We present the results from a series of three-dimensional finite element simulations modeling a high-speed train foundation utilizing various trackbed materials. Four trackbed materials were tested for their relative vibration attenuation capacities: ballast, concrete, conventional asphalt concrete, and rubber-modified asphalt concrete. Additionally, studies varying the speed and the weight of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…As a result, it will cause excessive acceleration in the upper layers. is was also found by other researchers [9,36]. However, at points B and C, the vertical acceleration experienced a reverse trend compared to the point A.…”
Section: Ickness Of the Asphalt Concrete Trackbed Versus Itssupporting
confidence: 86%
See 1 more Smart Citation
“…As a result, it will cause excessive acceleration in the upper layers. is was also found by other researchers [9,36]. However, at points B and C, the vertical acceleration experienced a reverse trend compared to the point A.…”
Section: Ickness Of the Asphalt Concrete Trackbed Versus Itssupporting
confidence: 86%
“…A number of experimental and numerical studies dedicated to assigning asphalt materials in both traditional ballasted and ballastless railway tracks were carried out. For example, Wang et al [9] conducted a comparative analysis of different paving materials such as asphalt concrete, rubbermodified asphalt concrete, concrete, and traditional ballast material in a ballasted track structure. e study concluded that rubber-modified asphalt concrete was the most effective material in reducing a ground-borne vibration produced by trains.…”
Section: Introductionmentioning
confidence: 99%
“…e influence of road unevenness on the free field vibrations was investigated. Wang et al [14] tested four trackbed materials for their relative vibration attenuation capacities and studied the effect of different speed and weight of the passing train on the performance of the paving materials. eir purpose is to reduce the adverse effects of pavement vibration on the surrounding structures and vehicles, rather than to analyze the pavement vibration signals for evaluating the pavement service condition.…”
Section: Introductionmentioning
confidence: 99%
“…Three different sub-ballast layers with the same thickness, equal to 200, made up respectively of concrete, asphalt and rubber asphalt were compared by Wang et al [17]. These researchers by means of a 3D FEM model calculated the RMS and the peak values of acceleration in comparison with a ballasted rail track without sub-ballast in several points at different distances from the rail track.…”
mentioning
confidence: 99%